Laser-induced fluorescence of rhodamine 6G cations in the gas phase: A lower bound to the lifetime of the first triplet state - Kordel, Mattias; Schooss, Detlef; Neiß, Christian; Walter, Lars; Kappes, Manfred M. (Journal of Physical Chemistry A, 2010)
We have studied the gas-phase laser-induced fluorescence of an ensemble of buffer gas-cooled Rhodamine 6G cations (R6G) stored in a quadrupole ion trap at 90 K. The fluorescence resulting from excitation with continuous-wave 488 nm radiation was observed to disappear almost completely on a time scale of seconds, dependent in detail on the excitation laser fluence. Such decay can be explained by the accumulation of R6G in a dark triplet state. This in turn facilitates the first lifetime determination of the lowest triplet state of free R6G by direct ground-state recovery measurements. A lower bound for the half-life was found to be ∼2 s. Adding oxygen in a volume fraction of 1% to the buffer gas leads to efficient quenching of the triplet state and correspondingly to complete suppression of the fluorescence intensity decay. Different rare gases were applied as buffers for collisional cooling, but no significant changes in the fluorescence properties were found. © 2010 American Chemical Society.